Second Five Year Plan Third Year's Progress 1958-59 Government of Kerala - Planning Commission (Planning Commission, 1958)
This publication is a review of the progress of the schemes included in the Second Five Year Plan during the Third Year of its implementation viz., 1958-1959. A comprehensive analysis of the progress in implementation of the schemes included in the Plan or a critical assessment of its performance is not attempted in this volume. This report gives only a broad perspective of the progress of the various schemes undertaken for execution during the year 1958-1959.
Government of Kerala